2022
DOI: 10.3390/infrastructures7080099
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Treated Waste Silt as Geopolymer Grouting Material and Filler for Semiflexible Pavements

Abstract: Considering the future shortage of natural aggregates, various researchers have promoted the recycling of by-products into various asphalt pavement types. This paper promoted a double-recycling technique, where thermally treated waste silt was used as a filler for the bituminous skeleton and grouting material of a geopolymer-based semiflexible pavement. Semiflexible pavements (SFP) inherit the flexibility of common asphalt pavements and simultaneously benefit from the rigidity of cement concrete pavements. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Te results showed that the samples formed by the cement grout with 30% milled glass presented the best mechanical performance. Solouki et al [18] used traditional cement-based cement and geopolymerbased cement as grouting materials to characterize porous and grouted samples in terms of indirect tensile strength (ITS), indirect tensile strength modulus (ITSM), and moisture sensitivity. Experimental results: it was shown that the control samples grouted with cement-based materials outperformed geopolymer grouting in all respects.…”
Section: Introductionmentioning
confidence: 99%
“…Te results showed that the samples formed by the cement grout with 30% milled glass presented the best mechanical performance. Solouki et al [18] used traditional cement-based cement and geopolymerbased cement as grouting materials to characterize porous and grouted samples in terms of indirect tensile strength (ITS), indirect tensile strength modulus (ITSM), and moisture sensitivity. Experimental results: it was shown that the control samples grouted with cement-based materials outperformed geopolymer grouting in all respects.…”
Section: Introductionmentioning
confidence: 99%